Becoming and staying physically active in adolescents with cerebral palsy: protocol of a qualitative study of facilitators and barriers to physical activity - Stewart Debra; Gorter Jan; Claassen Aniek AOM; Verschuren Olaf; Galuppi Barbara E; Shimmell Lorie J (BMC, 2011)
Abstract Background Adolescents with cerebral palsy (CP) show a reduced physical activity (PA). Currently there are no interventions for adolescents with CP in this critical life phase that optimise and maintain the individuals' physical activity in the long term. To develop such a program it is important to fully understand the factors that influence physical activity behaviours in adolescents with CP. The aim of this study is to explore what makes it easy or hard for adolescents with CP to be and to become physically active. Methods/Design A qualitative research method is chosen to allow adolescents to voice their own opinion. Because we will investigate the lived experiences this study has a phenomenological approach. Thirty ambulatory and non-ambulatory adolescents (aged 10-18 years) with CP, classified as level I to IV on the Gross Motor Function Classification System and 30 parents of adolescents with CP will be invited to participate in one of the 6 focus groups or an individual interview. Therapists from all Children's Treatment Centres in Ontario, Canada, will be asked to fill in a survey. Focus groups will be audio- and videotaped and will approximately take 1.5 hours. The focus groups will be conducted by a facilitator and an assistant. In preparation of the focus groups, participants will fill in a demographic form with additional questions on physical activity. The information gathered from these questions and recent research on barriers and facilitators to physical activity will be used as a starting point for the content of the focus groups. Recordings of the focus groups will be transcribed and a content analysis approach will be used to code the transcripts. A preliminary summary of the coded data will be shared with the participants before themes will be refined. Discussion This study will help us gain insight and understanding of the participants' experiences and perspectives in PA, which can be of great importance when planning programs aimed at helping them to stay or to become physically active.